Physiological stress response and recovery of an important estuarine fishery species, dusky kob Argyrosomus japonicus, after a simulated catch-and-release event. Issue 3 (1st October 2020) - Arkert, NK; Childs, A-R; Duncan, MI; Farthing, M; Potts, WM
Abstract : Catch and release (C&R) angling is a popular pastime the world over; however, studies have found that fish can experience considerable stress during a C&R event. To determine the effect of a C&R event on angled fishes, the physiological stress response (PSR) is often assessed. However, the peak PSR only occurs after a delay and is species-specific. The dusky kob Argyrosomus japonicus is a threatened species that is heavily exploited in South African estuarine fisheries. Given its collapsed-stock status, it is critical to understand the effects of C&R angling on the PSR of this species. The aim of this study was to plot the time-course of the PSR of A. japonicus to determine when the peak PSR occurs. Time had a significant effect on blood lactate ( p < 0.05) and glucose ( p < 0.05) levels, with both peaking 30–40 minutes after a stressor, but time did not have a significant effect on plasma cortisol levels ( p > 0.05). Blood lactate and glucose levels reached recovery by 150 minutes. The results suggest that blood sampling should be done 30–40 minutes after a stressor, and although A. japonicus is able to recover quickly from a C&R event, its delayed PSR may render it vulnerable to post-release predation.